Serum GDF-15 Levels in Patients with Parkinson's Disease, Progressive Supranuclear Palsy, and Multiple System Atrophy - Noriyuki Miyaue; Hayato Yabe; Masahiro Nagai (MDPI AG, 2023)
Serum growth differentiation factor 15 (GDF-15) levels are elevated in patients with Parkinson's disease (PD) and may help differentiate these patients from healthy individuals. We aimed to clarify whether serum GDF-15 levels can help differentiate PD from atypical parkinsonian syndromes and determine the association between serum GDF-15 levels and clinical parameters. We prospectively enrolled 46, 15, and 12 patients with PD, progressive supranuclear palsy (PSP), and multiple system atrophy (MSA), respectively. The serum GDF-15 level in patients with PD (1394.67 ± 558.46 pg/mL) did not differ significantly from that in patients with PSP (1491.27 ± 620.78 pg/mL; p = 0.573) but was significantly higher than that in patients with MSA (978.42 ± 334.66 pg/mL; p = 0.017). Serum GDF-15 levels were positively correlated with age in patients with PD (r = 0.458; p = 0.001); PSP (r = 0.565; p = 0.028); and MSA (r = 0.708; p = 0.010). After accounting for age differences, serum GDF-15 levels did not differ significantly between patients with PD and MSA (p = 0.114). Thus, age has a strong influence on serum GDF-15 levels, which may not differ significantly between patients with PD and atypical parkinsonian syndromes such as PSP and MSA.